A motivação dos peritos criminais das unidades técnico-científicas da Polícia Federal na Bahia - Durán, Maria Helena Carvalho (2012)
This study aimed at identifying which factors cause the motivation of the criminal experts of the technical units of the Brazilian Federal Police at the state of Bahia, in the development of their activities. For this purpose, a bibliographic, descriptive, explanatory and field research was performed. Individual and semi-open interviews were held, and the technique drawing construction was applied with all federal criminal experts stationed in Bahia, which amounts to 35 servants. Using the method of content analysis, 20 factors that influence the motivation of the staff members surveyed were identified; the 'salary' was shown to be the most encouraging factor in choosing the selective process for admission into the institution. The 'work itself', the 'challenge', the 'good working environment' and 'professional development' are the factors that most positively affect the motivation of criminal experts of the Federal Police at the state of Bahia. The 'professional appreciation', the 'feedback / result of the work', 'autonomy' and 'career growth' were considered important for the motivation, however, they are factors that for many of the respondents are not present or need to be improved in the Federal Police. The factors that impact negatively on the motivation of the referred experts is the lack of 'planning, organization', 'bureaucratic procedures, rigid hierarchy, inflexible structure, excess of control tools', 'the lack of equalitarian treatment', and the lack of 'integration with other components of the Federal Police'. Completing the list of the 20 factors that stood out in this study there are: 'the ways and work conditions', 'objectives / goals to be reached', 'beneficts', 'glamour / status / importance of the Federal Police', 'sense of responsibility', 'relationship with the managers' and 'personal / family matters'. The study suggests that a similar research should be conducted with Federal Criminal Experts stationed in other states and also with the other categories of servers in the institution.